The Effectiveness Scientific Approach through NHT Model to Improve Student’s SPS in Buffer - Ghalda Octavilani Halfa; Nina Kadaritna; Lisa Tania (Universitas Lampung, 2019)
This study was aimed to describe the effectiveness of the scientific approach through the NHT model to improve student’s science process skills (SPS) at buffer. The method in this research was quasi-experiment with pretest-posttest control group design. The population in this study were all students of XI MIPA class in Senior High Schools in Bandar Lampung 2018/2019 academic year. The sample of the research was chosen by the purposive sampling technique, XI MIPA 2 as the experimental class used the scientific approach through the NHT model and XI MIPA 1 as the control class used the conventional model. The technique of data analysis was used the parametric statistical test by independent sample t-test. The result showed an average of n-Gain SPS students in the experimental class greater than the average n-Gain SPS students in the control class. Based on the hypothesis test, there was a significant difference in the average n-Gain of SPS between the experiment class and the control class, show that the scientific approach through the NHT model was effective to improve student’s science process skills in the buffer. Keywords: buffer, NHT model, scientific approach, science process skills.Penelitian ini bertujuan untuk mendeskripsikan efektivitas pendekatan saintifik melalui model NHT untuk meningkatkan keterampilan proses sains siswa pada materi larutan penyangga. Metode penelitian yang digunakan adalah quasi experiment dengan Pretest and Postest Control Group Design. Populasi dalam penelitian ini adalah seluruh siswa kelas XI MIPA salah satu SMA di Bandar Lampung tahun ajaran 2018/2019. Sampel penelitian dipilih dengan teknik purposive sampling, yaitu kelas XI MIPA 2 sebagai kelas eksperimen yang menggunakan pendekatan sainifik melalui model NHT dan XI MIPA 1 sebagai kelas kontrol yang menggunakan pembelajaran konvensional. Teknik analisis data digunakan pada penelitian ini adalah uji statistik parametrik, yaitu uji independent sample t-test. Hasil penelitian menunjukkan bahwa rata-rata n-Gain KPS siswa pada kelas eksperimen lebih tinggi daripada rata-rata n-Gain KPS siswa pada kelas kontrol. Berdasarkan uji hipotesis, terdapat perbedaan rata-rata n-Gain KPS yang signifikan antara kelas eksperimen dan kelas kontrol, hal ini menunjukkan bahwa pendekatan saintifik melalui model NHT efektif untuk meningkatkan keterampilan proses sains siswa pada materi larutan penyangga. Kata kunci : KPS, larutan penyangga, model NHT, pendekatan saintifik.